Conceptul de răspundere administrativă şi formele ei - Pisarenco Olga (Revista Institutului Naţional de Justiţie, 2016)
In the national law, the administrative liability is confused with the contraventional liability. This impose an analyse of the concept of administrative liability, its peculiarities and the identification of liability forms that that incumbent the state public administration. The administrative liability is a category of the legal liability that establishes the deviations and administrative penalties for breaches of legal norms by the public authorities, authorities treated as public authorities and by officials of such authorities. However, there are discussions about the name of civil liability of the public administration and the civil servant, which is why we intend to address this issue.